Dust-dust collisions in cometary comas: applications to comet 67P/Churyumov-Gerasimenko - Planes, María Belén (2024)
Silica has emerged as a crucial component within inner comet comas. This work investigates silica dust aggregates and their interactions within cometary comas. We study the probability that aggregates in the size range 1-100 μm collide with each other in the coma and analyze the outcomes of such collisions by using the “Collision of Porous Aggregates” (CPA) Software, which incorporates mass, size, and porosity evolution of the dust population. Beginning with assumed initial distributions and physical properties for silica aggregates at the comet nucleus, we compute their collisional evolution from when they depart the nucleus until they traverse the coma. Using data of dust particles observed in the coma of comet 67P/Churyumov-Gerasimenko, we demonstrate that dust-dust collisions in cometary comas cannot be neglected. Our analysis yields final distributions in terms of mass, size, and porosity. To validate our findings, we compare them with in-situ measurements of 67P/Churyumov-Gerasimenko collected by the COSIMA (COmetary Secondary Ion Mass Analyser) instrument of the Rosetta mission. Our investigation reveals a notable agreement between our derived size distributions and the data acquired by COSIMA within the same size range. This study may be applied to any comet that presents a similar dust production as it approaches the Sun. The insights of this work may contribute to estimating other dust properties such as strength, absorption, reflectivity, and thermal conductivity and highlight the importance of considering dust-dust collisions when studying cometary comas and their evolution.